2017
DOI: 10.1007/s11228-017-0428-5
|View full text |Cite
|
Sign up to set email alerts
|

Maps with the Radon–Nikodým Property

Abstract: Abstract. We study dentable maps from a closed convex subset of a Banach space into a metric space as an attempt of generalize the Radon-Nikodým property to a "less linear" frame. We note that a certain part of the theory can be developed in rather great generality. Indeed, we establish that the elements of the dual which are "strongly slicing" for a given uniformly continuous dentable function form a dense G δ subset of the dual. As a consequence, the space of uniformly continuous dentable maps from a closed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition, it is shown that if (Γ, w * ) is discrete then every bounded operator T ∈ L(X, Y ) is Γ -flat. Let us also mention that the recently introduced notion of dentable map [11] implies Γ -flatness.…”
mentioning
confidence: 99%
“…In addition, it is shown that if (Γ, w * ) is discrete then every bounded operator T ∈ L(X, Y ) is Γ -flat. Let us also mention that the recently introduced notion of dentable map [11] implies Γ -flatness.…”
mentioning
confidence: 99%
“…Finally we will discuss the approximation by differences of convex functions in terms of the index of dentability improving [25,Theorem 1.4] and [15,Theorem 4.1]. A real function defined on a convex set is called DC-Lipschitz if it is the difference of two convex Lipschitz functions.…”
Section: Improving Functions and Domainsmentioning
confidence: 99%